1979
DOI: 10.1002/jbm.820130614
|View full text |Cite
|
Sign up to set email alerts
|

A new surface treatment for bonding

Abstract: Bonding resins to enamel requires some form of mechanical attachment. Currently the dissolution of the outermost enamel layer is involved in etching with phosphoric acid. A new approach to mechanical bonding is described using a crystalline interface which itself bonds chemically to enamel. The crystals can be removed from the enamel with an ultrasonci or sickle-scaler followed by pumice prophylaxis. Many variations of the crystal growth principle may be visualized, including the development of fluoride-contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

1982
1982
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 4 publications
0
19
0
2
Order By: Relevance
“…However, several other studies have suggested maximum bond forces of 35. 6 N 16) and 97.88 N 17) . These various outcomes and the wide range of values are probably the result of differences in testing devices.…”
Section: Discussionmentioning
confidence: 94%
“…However, several other studies have suggested maximum bond forces of 35. 6 N 16) and 97.88 N 17) . These various outcomes and the wide range of values are probably the result of differences in testing devices.…”
Section: Discussionmentioning
confidence: 94%
“…24,25 They were adequate according to McSherry, 26 Wheeler and Ackerman, 27 and Keizer et al 28 However, the bond strengths obtained in this study are low based on the recommendations (97.88 N) of Maijer and Smith. 29 The wide-ranging differences in reported bond strengths are probably due to various methods used to measure bond strength. 30 Wire loops, steel rods, and steel plates have all been utilized to determine shear bond strength.…”
Section: Discussionmentioning
confidence: 99%
“…Hossain et al 12 reported an increase in the calcium to phosphorus ratio achieved during laser irradiation, which leads to caries inhibition. 16,17 Therefore, laser irradiation might have an advantage as an etchant for orthodontic bonding. In previous studies [7][8][9] , cutting of enamel and dentine with laser systems was established.…”
Section: Discussionmentioning
confidence: 99%